Petrogenesis of the Northwest Africa 4898 high‐Al mare basalt. (4th May 2016) - Li, Shaolin; Hsu, Weibiao; Guan, Yunbin; Wang, Linyan; Wang, Ying
Abstract: Northwest Africa (NWA) 4898 is the only low‐Ti, high‐Al basaltic lunar meteorite yet recognized. It predominantly consists of pyroxene (53.8 vol%) and plagioclase (38.6 vol%). Pyroxene has a wide range of compositions (En12–62 Fs25–62 Wo11–36 ), which display a continuous trend from Mg‐rich cores toward Ca‐rich mantles and then to Fe‐rich rims. Plagioclase has relatively restricted compositions (An87–96 Or0–1 Ab4–13 ), and was transformed to maskelynite. The REE zoning of all silicate minerals was not significantly modified by shock metamorphism and weathering. Relatively large (up to 1 mm) olivine phenocrysts have homogenous inner parts with Fo 74 and sharply decrease to 64 within the thin out rims ( 30 μm in width). Four types of inclusions with a variety of textures and modal mineralogy were identified in olivine phenocrysts. The contrasting morphologies of these inclusions and the chemical zoning of olivine phenocrysts suggest NWA 4898 underwent at least two stages of crystallization. The aluminous chromite in NWA 4898 reveals that its high alumina character was inherited from the parental magma, rather than by fractional crystallization. The mineral chemistry and major element compositions of NWA 4898 are different from those of 12038 and Luna 16 basalts, but resemble those of Apollo 14 high‐Al basalts. However, the trace element compositions demonstrate that NWA 4898 and Apollo 14 high‐Al basalts could not have been derived from the same mantle source. REE compositions of its parental magma indicate that NWA 4898 probably originated from a unique depleted mantle source that has not been sampled yet. Unlike Apollo 14 high‐Al basalts, which assimilated KREEPy materials during their formation, NWA 4898 could have formed by closed‐system fractional crystallization.